Cosmopolitanism in Kant’s Anthropology from a Pragmatic Point of View: Regulative Ideas and Empirical Evidence - Pasquarè, Roberta (Con-Textos Kantianos. International Journal of Philosophy, 2019)
With this paper I analyze Kant’s account of the human vocation to cosmopolitanism discussed in the last section of the Anthropology from a Pragmatic Point of View (7:321-333) and show how Kant’s notion of cosmopolitanism requires the cooperation of pure reason and pragmatic anthropology. My main thesis is that pure reason provides regulative ideas, thereby maintaining a foundational role, and pragmatic anthropology provides empirical evidence, thereby reinforcing the theoretical and practical status of reason’s ideas. In developing my analysis, I argue that Kant reframes the question ‘What is the human being?’ in a non-essential way, foregrounds a moral practical concern, and assigns freedom an unprecedented role. Finally, I relate my analysis to two questions frequently discussed in Kant scholarship, namely the problem of whether the Anthropology has only a pragmatic or also a moral scope and the problem of the relation between the Anthropology and Kant’s critical system.